2020
DOI: 10.1038/s41598-020-59564-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Fissure Sealant and Fluoride Varnish on Caries Prevention for First Permanent Molars: a Systematic Review and Meta-analysis

Abstract: The high prevalence and heavy socioeconomic burden for caries of first permanent molars (FPMs) make the prevention of this disease a major public health goal. Current guidelines recommend a preference of fissure sealant (FS) over fluoride varnish (FV) based on two recent systematic reviews. However, evidences of these two studies are weak because of scarce data and some limitations. Besides, an upto-date large scale randomized controlled trial (RCT) reported commensurate effectiveness of these two techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 25 publications
4
36
0
3
Order By: Relevance
“…A recent meta-analysis showed that over a 2-3-year follow-up period, there was no statistical difference in the incidence of occlusal caries on first permanent molars following sealant and FV application [23]. These findings corroborate those of Chestnutt et al who found that the effectiveness of FV in preventing occlusal decay on first permanent molars was higher but not statistically different from sealants (caries incidence 17.5% vs. 19.6%) following a 3-year period.…”
Section: Chemical Management Of Caries Using Fluoride Varnishmentioning
confidence: 99%
“…A recent meta-analysis showed that over a 2-3-year follow-up period, there was no statistical difference in the incidence of occlusal caries on first permanent molars following sealant and FV application [23]. These findings corroborate those of Chestnutt et al who found that the effectiveness of FV in preventing occlusal decay on first permanent molars was higher but not statistically different from sealants (caries incidence 17.5% vs. 19.6%) following a 3-year period.…”
Section: Chemical Management Of Caries Using Fluoride Varnishmentioning
confidence: 99%
“…Los barnices de fluoruro aplicados tópicamente se han utilizado ampliamente como una intervención no invasiva para el tratamiento de lesiones de caries. La aplicación de barnices de flúor dos veces al año, en la dentición primaria o permanente, está asociado a una reducción significativa de la aparición de lesiones de caries dental, [9][10][11] teniendo en cuenta la condición de la desmineralización dental. Su efecto relativo está relacionado con el nivel de riesgo de caries y con la exposición a otras fuentes de flúor, 9 la concentración recomendada es del 5%.…”
Section: Barniz De Flúorunclassified
“…Su uso en molares permanentes en erupción también se indica para prevenir la desmineralización, con dos aplicaciones anuales. 11…”
Section: Barniz De Flúorunclassified
See 2 more Smart Citations